Confirmation of Lithophyllum trincomaliense comb. & stat. nov. and of L. validum (Corallinales, Rhodophyta) as distinct species based on genetic and morpho-anatomical analyses of type material. Issue 6 (2nd November 2022) - Kato, Aki; Muangmai, Narongrit; Baba, Masasuke
ABSTRACT: The non-geniculate coralline alga Lithophyllum okamurae includes two infraspecific taxa, L. okamurae f. trincomaliense and L. okamurae f. validum (currently regarded as an independent species, L. validum ), which were described from Sri Lanka solely on the basis of morpho-anatomical features. We investigated the taxonomic status of these two taxa using comparable DNA sequence data ( psb A, rbc L, partial LSU rDNA, and COI) and complementary morpho-anatomical features from type material and from specimens whose sequences were linked to type material. Our molecular analyses showed that both taxa are well-defined and are adequately treated as independent species, and that they are distantly related to L. okamurae . Morpho-anatomically, L. trincomaliense and L. validum were nearly indistinguishable, both possessing well-developed fruticose thalli and lacking trichocytes, the only distinguishable features being the shapes of the branch tips (round for L. trincomaliense vs flattened for L. validum ). The present study confirmed two Lithophyllum species from the Indian Ocean. Seven infraspecific taxa have been ascribed to L. okamurae ; one was shown to be conspecific and four are now confirmed to be distinct species, including the two infraspecific taxa investigated in the current study.